Cranial computerrized tomography in the evaluaaton of stroke patients in Ibadan (2003)
206 patients clinically diagnosed as stroke/cerebrovascular accidents (CVA) were investigated using computerized tomography (CT) scan. 19 patients(9%) had normal scan, while 20(9.7%) patients had other lesions including atrophy and tumours. Of the 167 (18.1%) patients proven to have suffered a cerebro-vascular accidents (CVA/ stroke), 73(43.7%) were haemorrhagic, 92(55.1%) were infarcts; and left side when it is heaemorrhagic than infarct (16.7%;38.3). The parietal and frontal lobes were affected when lesions occur in single site while caudate nucleus, putamen and ventricles are commonly affected when lesion is in more that 2 sites. The occipital lobe i.e. posterior cerebral artery territory is infrequently involved.